Structure-based inhibitor design and repurposing clinical drugs to target SARS-CoV-2 proteases. (28th February 2022) - Narayanan, Anoop; Toner, Shay A.; Jose, Joyce
Abstract : SARS-CoV-2, the coronavirus responsible for the current COVID-19 pandemic, encodes two proteases, 3CL pro and PL pro, two of the main antiviral research targets. Here we provide an overview of the structures and functions of 3CL pro and PL pro and examine strategies of structure-based drug designing and drug repurposing against these proteases. Rational structure-based drug design enables the generation of potent and target-specific antivirals. Drug repurposing offers an attractive prospect with an accelerated turnaround. Thus far, several protease inhibitors have been identified, and some candidates are undergoing trials that may well prove to be effective antivirals against SARS-CoV-2.